Biomechanics of P-Selectin PSGL-1 Bonds: Shear Threshold and Integrin-Independent Cell Adhesion - Xiao, Zhihua (Biophysical Society, 2006)
Platelet-leukocyte adhesion may contribute to thrombosis and inflammation. We examined the heterotypic interaction between unactivated neutrophils and either thrombin receptor activating peptide (TRAP)-stimulated platelets or P-selectin-bearing beads (Ps-beads) in suspension. Cone-plate viscometers were used to apply controlled shear rates from 14 to 3000/s. Platelet-neutrophil and bead-neutrophil adhesion analysis was performed using both flow cytometry and high-speed videomicroscopy. We observed that although blocking antibodies against either P-selectin or P-selectin glycoprotein ligand-1 (PSGL-1) alone inhibited platelet-neutrophil adhesion by ∼60% at 140/s, these reagents completely blocked adhesion at 3000/s. Anti-Mac-1 alone did not alter platelet-neutrophil adhesion rates at any shear rate, though in synergy with selectin antagonists it abrogated cell binding. Unstimulated neutrophils avidly bound Ps-beads and activated platelets in an integrin-independent manner, suggesting that purely selectin-dependent cell adhesion is possible. In support of this, antagonists against P-selectin or PSGL-1 caused dissociation of previously formed platelet-neutrophil and Ps-bead neutrophil aggregates under shear in a variety of experimental systems, including in assays performed with whole blood. In studies where medium viscosity and shear rate were varied, a shear threshold for P-selectin PSGL-1 binding was also noted at shear rates <100/s when Ps-beads collided with isolated neutrophils. Results are discussed in light of biophysical computations that characterize the collision between unequal-size particles in linear shear flow. Overall, our studies reveal an integrin-independent regime for cell adhesion and weak shear threshold for P-selectin PSGL-1 interactions that may be physiologically relevant.